Phytochemical Screening and Antimicrobial Potentialo of Halodule Pinifolia: Life Sciences-Microbiology - Mary, S. Jenita Gnana; Bharathidasan, R.; Ramamurthy, V. (International Journal of Life Science and Pharma Research, 2022)
The aim of this work was to study the phytochemical and antimicrobial activity of seagrass extracts of Halodulepinifolia on clinical isolated pathogens. Seagrass species have very potential groups producing several secondary metabolites. The bioactive potential of seagrass species viz., Halodulepinifolia occurring commonly along the Thanjavur coastal area was selected. We evaluate the phytochemical and antimicrobial potential of different extracts of Halodulepinifolia. The extract of the seagrass was tested against E.coli, B.subtilis, A.nigerand C.albicans by agar diffusion method. Phytochemical screening revealed the presence of carbohydrates, reducing sugars, alkaloids, saponins, phenolic compounds and flavonoids in aqueous seagrass extract. The results of the present study conclude that the studied plant possesses broad-spectrum antimicrobial properties and may act as a potent antioxidant for biological systems susceptible to free radical-mediated reactions.